2023
DOI: 10.1200/jco.22.00291
|View full text |Cite
|
Sign up to set email alerts
|

A Phase III Study of Pafolacianine Injection (OTL38) for Intraoperative Imaging of Folate Receptor–Positive Ovarian Cancer (Study 006)

Abstract: PURPOSE The adjunctive use of intraoperative molecular imaging (IMI) is gaining acceptance as a potential means to improve outcomes for surgical resection of targetable tumors. This confirmatory study examined the use of pafolacianine for real-time detection of folate receptor–positive ovarian cancer. METHODS This phase III, open-label, 11-center study included subjects with known or suspected ovarian cancer, scheduled to undergo cytoreductive surgery. The objectives were to confirm safety and efficacy of pafo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 26 publications
0
63
0
Order By: Relevance
“…A literature search of 2817 results yielded 24 clinical studies to be included in our review 16–39. The study inclusion process is illustrated in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…A literature search of 2817 results yielded 24 clinical studies to be included in our review 16–39. The study inclusion process is illustrated in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The latest phase‐3 trial (NCT03180307) showed that 47 of 109 patients with OC underwent additional resections, for tumours that were detected by the fluorescence signal of OTL38 but were invisible in white light and were undetectable by palpation 62 . Moreover, OTL38 showed a limited safety risk in all trials and steady sensitivity, ranging from 83% to 85%.…”
Section: Eoc‐targeted Fluorescent Probesmentioning
confidence: 99%
“…This approach allows for delineation of tumors from normal tissues in real time to enable safer and more effective removal of cancerous lesions. 1 Increasing evidence suggests that the chemical features of the fluorescent label can strongly influence the in vivo imaging properties of bioconjugates, including their specificity and ability to generate contrast. 2 , 3 Thus, dye selection is critical and has recently emerged as a key technical element of FGS research.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence-guided surgery (FGS) is a method of enhancing intraoperative visualization of tumors, which may be difficult to discern, often through the use of exogenously administered contrast agents that target tumor tissues. This approach allows for delineation of tumors from normal tissues in real time to enable safer and more effective removal of cancerous lesions . Increasing evidence suggests that the chemical features of the fluorescent label can strongly influence the in vivo imaging properties of bioconjugates, including their specificity and ability to generate contrast. , Thus, dye selection is critical and has recently emerged as a key technical element of FGS research. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation